GAMBARAN ULTRASONOGRAFI TESTIS DAN EPIDIDIMIS KAMBING KACANG (Capra hircus) DI WILAYAH LAHAN KERING KEPULAUAN - Gaina, Cynthia Dewi; Foeh, Nancy D. F. K.; Tophianong, Tarsisius C. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
This research aims to study testis and epididymis of dry land goat (Capra hircus) on B-mode ultrasound imaging. Twelve adult local male goats were examined to study normal testes and epididymis ultrasonic appearances. B-mode real time scanner with a 7.5 MHz, linear array transducer was used to evaluate the echotexture of the testicular parenchyma, mediastinum and the epididymis. The testicular parenchyma was represented uniformly homogenous and moderately echogenic with the mediastinum was more highly echogenic. The epididymal head appeared less echogenic but homogenous in structure, while the epididymal tail was more heterogeneous and less echogenic than the testis. Each structure in male reproductive organ, the testis, head and tail of epididymis can be differentiated using ultrasound imaging, but body epididymis was difficult to identify. It is concluded that ultrasound can be as a valuable diagnostic tool to investigate the health of male goat reproductive organ.